STATE RESPONSES AND THE DYNAMICS OF COMMUNAL CONFLICT IN EBONYI STATE: THE ABAKALIKI–IKWO EXPERIENCE - Aro, Gilbert Chukwu; Onyekere, Faith Ngozi; Okolie, Anselem Onyekachi; Nnadi, Samuel (African Journal of Social and Behavioural Sciences, 2025)
In recent decades, conflict has been on the increase globally, and its dimensions touch on ethnic, religious, political, economic, nationalistic, and territorial contestations. One of the major reasons for this disturbing rise in conflict cases across the world is land and boundary disputes. Land constitutes an important resource that humans struggle to acquire for themselves, such that more is never enough. Over time, the communal conflict between Eyigba and Eyibichiri communities in Izzi and Ikwo Local Government Areas, respectively, has claimed lives and properties. More than 50 people have lost their lives to this protracted conflict, many have been rendered homeless, and socio-economic activities have been disrupted, even forcing the staff and students of Alex Ekwueme Federal University, Ikwo, to stay away from school for fear of violence. The study sets out to examine the responses of the Ebonyi State Government under the leadership of David Nweze Umahi to this protracted violent conflict. The study is descriptive, and data were obtained from secondary sources, using the Opportunity Structure Theory as its framework of analysis. The findings reveal that the lack of extensive and systematic peace-building and advocacy blueprints, as well as the reactive rather than proactive mechanisms employed by the government, are responsible for the continual outbreaks. The study recommends preventive mechanisms such as land and boundary control laws and sustainable peace-building blueprints to ensure lasting peace in the state.